PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP HASIL BELAJAR SISWA KELAS III SD NEGERI 101743 HAMPARAN PERAK TAHUN PEMBELAJARAN 2023/2024 - Vini Selvia Sijabat; Ribka Kariani Sembiring; Patri Janson Silaban; Antonius Remigius Abi; Anton Sitepu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the effect of the Jigsaw Type Cooperative learning model on the learning outcomes of class III students. This research method is descriptive quantitative. The research population was class III students at State Elementary Schools in Hamparan Perak, totaling 86 students. Sampling was taken using random sampling and 30 students were used in class III at SD Negeri 101743. The results of this research show that student learning outcomes are in the very good category with 78.2. By testing the correlation, it can be seen that the correlation coefficient is rcount (0.845) ≥ rtable (0.361), so ha is accepted. There is an influence of the Jigsaw Type Cooperative model on the learning outcomes of class III students at SD Negeri 101743 Hamparan Perak. It can also be seen from the t-test where tcount ≥ ttable, namely 8.458 ≥ 2.042, thus stating that ha is accepted. This shows that there is a significant positive influence from the use of the Jigsaw Type Cooperative model on the learning outcomes of class III students at SD Negeri 101743 Hamparan Perak for the 2023/2024 Academic Year.